Molecular Docking Tool: General Concept and Recent Advances - Biswaranjan Ray; Amiyakanta Mishra; Chinmaya Kesari Sahoo (Recent Developments in Chemistry and Biochemistry Research Vol. 1, 2024)
This study explores about general concept and recent advances of molecular docking. Molecular docking is a computational method used to predict the interaction of two molecules generating a binding model. In many drug discovery applications, docking is done between a small molecule and a macromolecule for example, protein-ligand docking. The molecular docking approach can be used to model the interaction between a small molecule and a protein at the atomic level, which allow us to characterize the behavior of small molecules in the binding site of target proteins as well as to elucidate fundamental biochemical processes. The simulation of the docking process as such is a much more complicated process in this approach, the protein and the ligand are separated by some physical distance, and the ligand finds its position into the protein’s active site after a certain number of “moves” in its conformational space. The present Review focus Concept, Strategy, Types and other Aspects with Recent Advances of Molecular Docking. It is concluded that molecular docking has been able to identify promising compounds that might represent future solutions in critical areas of human health.